The influence of climatic factors on the quality of grapes in the vineyards Murfatlar and Iasi - V. Artem; A.Ranca; C.Ciobanu; I.Dina; A.Nechita; G.Zaldea (Romanian Journal of Horticulture)
The objective of the present study was to evaluate the influence of key climatic factors (temperature and precipitation) during the growing season on the ripening and chemical composition of grapes for white and red wines in two vineyards renowned for the quality of their wines: Murfatlar and Iași, over two consecutive years (2023 and 2024). The climatic variability, characterized by high air temperatures and prolonged periods without precipitations contributed to a forced ripening of the grapes, with harvesting taking place in 2024 one week earlier than in 2023 in both vineyards. The high temperatures during ripening accelerated the accumulation rate of sugars, resulting in concentrations exceeding 200 g/L for white wine grape varieties and over 220 g/L for red wine grape varieties in the Murfatlar wine center, and concentrations ranging between 192.6-206.0 g/L for white grape varieties and 200.7-221.0 g/L for red grape varieties in the Copou Iași wine center. The results obtained, analyzed statistically, highlighted significant differences in the primary metabolites of grape berries (sugars and organic acids), influenced by vineyard and climatic conditions over the two studied years. Maintaining traditional viticultural regions remains a challenge for producers, requiring various strategies to compensate for these imbalances and to produce high-quality, balanced wines.